The field of wacky inventions - Carman, Patrick (New York : Scholastic Press, 2013)
Leo and Remi have gotten used to the strangeness of the Whippet Hotel, but when the entire top floor is hoisted into the sky and transported to the field of wacky inventions, they find that they must compete against a number of foes to solve a puzzle or lose their beloved hotel forever.
O
b
b
Keywords: Hotels -- Juvenile fiction; Puzzles -- Juvenile fiction; Adventure stories; Hotels, motels, etc. -- Fiction; Puzzles -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction; Mystery fiction